Development and Study of Ezzence: A Modular Scent Wearable to Improve Wellbeing in Home Sleep Environments - Amores, Judith; Dotan, Mae; Maes, Pattie (Frontiers in Psychology, 2022)
Ezzence is the first smartphone-controlled olfactometer designed for both day and night conditions. We discuss the design and technical implementation of Ezzence and report on a study to evaluate the feasibility of using the device in home-based sleep environments. The study results (n=40) show that subjects were satisfied with the device and found it easy to use. Furthermore, participants reported a significant improvement in sleep quality when using the device with scent in comparison to the control condition (P=0.003), as well as better mood the following morning (P=0.03) and shorter time to sleep onset (P=0.008). The device is integrated with a wearable EEG and real-time sleep staging algorithm so scent can be released during specific sleep stages, N1, N2, N3, and REM, which is important for certain use cases. Ezzence can be used for several applications, including those that require that scent is triggered during day and night. They include targeted memory reactivation, longitudinal health treatments, therapy, and mental or physical exercises. Finally, this paper proposes an interaction framework to understand relationships between smells and environments based on proxemic dimensions and passive or active interactions during sleep.